Arquitetura e Cotidiano Escolar: A Produção Curricular nas Séries Finais do Ensino Fundamental da Escola Córrego do Milanez/São Mateus-ES - Santos, Samuel Pinheiro da Silva (2020)
This research investigates the curricular production of the Córrego do Milanez Elementary School/São Mateus-ES, by analyzing the school daily life with focus on the architecture, the guiding documents and their pedagogical practices. Focusing on the bro